PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA UMKM YANG DI MEDIASI OLEH MANAJEMEN RANTAI PASOKAN HIJAU PADA UMKM KERAJINAN KAYU DI DAERAH ISTIMEWA Yogyakarta - Najah, Miftahun; Kusmantini, Titik; Sugandini, Dyah (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2024)
The research was conducted with the aim of: (1) to examine the effect of intellectual capital and GSCM on the performance of UMKM. (2) to examine the effect of GSCM as a mediating variable on the relationship between intellectual capital and MSME performance. The sample in this study is 95 wood craft UMKM in the Special Region of Yogyakarta that are registered in the Legality and Sustainability Information System (SILK), namely 143 UMKM. The quantitative method was tested using Partial Least Square (PLS). The research proved that the performance of wood craft UMKM registered in the Legality and Sustainability Information System (SILK) in the Special Region of Yogyakarta is influenced by intellectual capital and green supply chain management. This study also found a mediating effect of green supply chain management on the relationship between MSME performance and MSME performance.